Kristalisasi Butir Pancasila sebagai Fondasi Hukum Budaya di Republik Indonesia - Maria Yeti Andrias; Zonita Zirhani Rumalean (UNES Law Review, 2023)
This paper aims to deepen the understanding of the Pancasila concept as a legal source within the context of national culture in the framework of the unitary state of the Republic of Indonesia. The research employs a documentary literature review approach. The analysis results conclude that "Panca" signifies five, while "Sila" refers to principles or principles encompassing essential values such as belief in the Almighty, humanity, nationalism, democracy, and social justice. The article explores the manifestation of Pancasila values and concepts in culture by referring to three main concepts: cultural materials, where individuals are considered cultural realities; social interactions; and tangible creative products. The analysis, study, and description provided in this paper lay the foundation for practical recommendations, emphasizing the necessity of embodying Pancasila values and applying these concepts as a national legal foundation. Beyond mere text, the embodiment of Pancasila values must be an integral part of the daily actions of all citizens. This article advocates for the crucial implementation of concrete Pancasila values in societal life, forming a solid foundation for cultural law in Indonesia.